2020
DOI: 10.1186/s12891-020-3130-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and experience of arthroscopic lateral patella retinaculum releasing through/outside synovial membrane for the treatment of lateral patellar compression syndrome

Abstract: Background: Arthroscopic closure release includes arthroscopic lateral patella retinaculum releasing (LPRR) either outside synovial membrane (OSM) or through synovial membrane (TSM). At present, there is no research to compare the clinical efficacy of the above two methods for the treatment of lateral patellar compression syndrome (LPCS). So, the goal of this study was to investigate the method and overcome of arthroscopic LPRR either OSM or TSM for the treatment of LPCS. Methods: From September 2014 to Decemb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Trochlear dysplasia, Install-Salvati ratio ranging from 1.0 and 1.2, and tibial tubercle-trochlear groove (TT-TG) greater than 22 mm also have been evaluated [ 69 , 70 ]. Another cause of persistent pain and possible chondral damage is the lateral patellar compression syndrome (LPCS) [ 71 , 72 ]. LPCS presents shortened and tightened lateral retinacular combined with lateral patellar tilt, with overload of the lateral patellar articular compartment and patellar mal-tracking [ 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trochlear dysplasia, Install-Salvati ratio ranging from 1.0 and 1.2, and tibial tubercle-trochlear groove (TT-TG) greater than 22 mm also have been evaluated [ 69 , 70 ]. Another cause of persistent pain and possible chondral damage is the lateral patellar compression syndrome (LPCS) [ 71 , 72 ]. LPCS presents shortened and tightened lateral retinacular combined with lateral patellar tilt, with overload of the lateral patellar articular compartment and patellar mal-tracking [ 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Verdonk et al [ 25 ] compared the results of knee CT examination before and after LR release surgery and found that the procedure can effectively improve the morphology of the patient’s patellofemoral joint. Arthroscopic closing LR release for the treatment of ELPS can effectively improve the function and relieve symptoms of patellofemoral joint with the advantages of small trauma, rapid recovery and less complications [ 27 ]. In our study, similar results were found that Kujala score and Lysholm score were significantly increased at the last follow-up compared with that before surgery, indicating significant improvement in knee function.…”
Section: Discussionmentioning
confidence: 99%
“…The synovial membrane, joint capsule, and LR were partially or totally cut off, which easily caused complications of intra-articular hemorrhage and joint adhesion, which affected curative effect [ 10 ]. Therefore, we performed LR release from the surface of LR to preserve synovium and capsule of joint, so as to reduce the risk of joint hematoma and adhesion [ 27 ]. In our study, manipulation under anesthesia for knee contracture due to postoperative adhesion was required in only 3 patients, and joint hematoma has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…When I compared current study with other studies that exclusively analyzed lateral patellar release or viscosupplementation, I can find the following important points: Chen et al [ 31 ] reported that arthroscopic lateral patellar retinacular release can effectively improve function and symptoms of patellofemoral joint in patients with lateral patellar compression syndrome. In current study, there was improvement after lateral release with better results after intraarticular injection of Hyaluronic acid as those patients, who are involved in current study, had degenerative changes in patellofemoral joint.…”
Section: Discussionmentioning
confidence: 99%